Moment-based dissipative observer design for cell population balance models⁎Funded by the Deutsche Forschungsgemeinschaft (DFG, German Research Foundation) – Project-ID 395461267. Issue 3 (2021) - Schaum, A.; Jerono, P.; Meurer, T.; Moreno, J.A.
Abstract: A dissipativity-based observer design for a class of cell population balance models is presented and evaluated using experimental data. The population balance model is described by a partial integro-differential equation coupled with an ordinary differential equation for a batch bioreactor with biomass measurement via an optical density sensor. The dissipative observer is proven to exponentially converge in the first moment of the cell size distribution and the substrate concentration in the absence of modeling and measurement errors. The theoretical results are evaluated using experimental data from a 2 liter lab-scale reactor for anaerobic yeast fermentation on glucose using nitrogen gas supply, showing a good performance of the dissipativity-based estimation scheme.